Integration of Blockchain-Based Smart Contracts as a Solution for Automation and Sharia Compliance in Islamic Banking Products - Cahyani, Adinda Intan; Baidhowi (Law Research Review Quarterly, 2025)
The integration of blockchain-based smart contracts technology has emerged as an innovative solution in banking. The utilization of blockchain technology and smart contracts offers great potential in improving operational efficiency and compliance with Shariah principles in Islamic banking products. Overall, blockchain-based smart contracts have the potential to overhaul the traditional way of providing Islamic banking services, by providing more efficient, transparent, and inclusive solutions. This research emphasizes the need for technological readiness and supportive policies for the successful implementation of this technology in the Islamic banking sector. This article discusses the potential use of smart contracts in strengthening automation and sharia compliance in Islamic banking products, focusing on the role smart contracts can play in increasing Islamic financial inclusion and expanding access to Islamic banking services and how prepared Islamic financial institutions are to adopt blockchain technology and smart contracts. That way, the utilization of blockchain-based smart contracts integration can be seen as better to bring significant changes in the Islamic banking sector, both in terms of increasing efficiency and in strengthening sharia principles which are the main foundation of the Islamic financial system.